Antifungal and synergistic activity of five plant essential oils from Serbia against Trichoderma aggressivum f. europaeum Samuels & W. Gams - Luković, Jelena; Đurović-Pejčev, Rada; Đorđević, Tijana; Milijašević-Marčić, Svetlana; Duduk, Nataša; Vico, Ivana; Potočnik, Ivana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Five essential oils isolated from plants originating from Serbia and ten combinations of the selected essential oils were assayed to test their inhibitory and fungicidal activity against Trchoderma aggressivum f. europaeum Samuels & W. Gams using two distinctive methods: microdilution and fumigant macrodilution methods. The strongest activity was demonstrated by spearmint (Mentha spicata L.) and thyme (Thymus serpyllum L.) oils at the minimum inhibitory concentration (MIC) of 6.25 ml ml-1 using microdilution, and 0.16 ml ml-1 of air using fumigant macrodilution method. The antifungal activity of basil (Ocimum basilicum L.) and peppermint (Mentha piperita L.) was medium, while the oil extracted from St. John’s wort (Hypericum perforatum L.) exhibited the lowest activity. None of the selected essential oils exhibited fungicidal effect at minimal fungicidal concentrations (МFC) of over 25 ml ml-1 or 0.32 ml ml-1of air, using micro- and macrodilution, respectively. When microdilution was used, the strongest antifungal activity was demonstrated by two oil combinations: spearmint-thyme and spearmint-peppermint, having MIC and MFC values of 3.75 ml ml-1. The lowest activity was demonstrated by the basil-St. John’s wort essential oil combination, at 30 ml ml-1 MIC, and MFC exceeding 30 ml ml-1. The obtained results indicate possible synergistic effects of essential oils and their components.